2020
DOI: 10.3390/s20247156
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Strength Level on the Acute Post-Activation Performance Enhancement Following Flywheel and Free Weight Resistance Training

Abstract: This study aimed to compare the post-activation potentiation performance enhancement (PAPE) response to the acute inertial flywheel (FW) and free weight resistance training (TRA) on subsequent countermovement jump (CMJ) and sprint performance (10 m sprint). This study used a randomized crossover design including twenty-eight healthy males that were divided into strong (relative one-repetition maximum (1RM) back squat > 2.0 × body mass) and weak (relative 1RM back squat < 2.0 × body mass) groups. All part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…In addition, these statistically significant results are consistent with their moderate effect sizes, as depicted in Table 3 , showing practical significance for the improvement percentage and the jump height reached in the CMJ in the Post-test. Hence, our study suggests that a conditioning activity would generate a positive effect on VJ performance, i.e., PAPE, as a result of an increase in muscle strength obtained 8 min after activation protocol [ 29 , 31 , 47 , 52 , 56 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, these statistically significant results are consistent with their moderate effect sizes, as depicted in Table 3 , showing practical significance for the improvement percentage and the jump height reached in the CMJ in the Post-test. Hence, our study suggests that a conditioning activity would generate a positive effect on VJ performance, i.e., PAPE, as a result of an increase in muscle strength obtained 8 min after activation protocol [ 29 , 31 , 47 , 52 , 56 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, contradictory results were found in the reviewed literature: the improvements in VJ found by Dobbs et al (2018) were not statistically significant. In addition, some authors did not find effects on jumping performance after a PAP protocol [ 14 , 26 , 27 , 28 , 29 , 30 ]. Furthermore, the persistence of PAP is significant only for a limited period of time from 28 s to less than 3 min [ 31 ], obtaining the performance peak improvement (PAPE) at 6–20 min [ 25 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although speed is currently the most commonly used variable to monitor loading intensity in real-time for ISO-load [2,10,11], power is more widely used in FRTD [4]. However, a recent work showed that angular acceleration is more sensitive to changes in load in leg extension exercise executed on an FRTD [30].…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of differences in training effects between FW-load and ISO-load has been of great interest [8][9][10][11][12][13][14]. In these studies, a higher mechanical demand on the knee extensors [9], increased metabolic demands [10], comparable muscle hypertrophy [13], and higher eccentric muscle activity [8] were observed when FW-loads were used in comparison with ISO-loads.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation